Supper Sole / Nuraeni Ondin … [et al.] - Ondin, Nuraeni; Muhd Faizal, Syaza Adilah; Syed Muhammad, Sharifah Faqihah Ilyana; Abdul Raman, Nur Amni; Kamis, Rohaiza (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Shoes are one of the necessities, particularly for those who are blind or have other difficulties with vision. But recently, there have been a lot of complaints about the pain and losses these shoes cause their wearers. It's because they engage in physically demanding routine activities. These include things like smashed or damaged shoes and feet slippery shoes that could fall on someone, and more. To solve this problem, we have already innovated a 2 in 1 shoe which is a shoe named SUPPER SOLE. The SUPPER SOLE is a revolutionary 2-in-1 shoe designed to provide comfort and mobility to visually impaired students. Its replaceable soles prioritize traction and stability, while neodymium magnets ensure safety and adaptation to various environments. The shoe aims to improve safety, comfort, and independence for visually impaired students in educational settings. The shoe's design is innovative and creative, offering fully adjustable interchangeable soles, easily navigable Neodymium Magnet technology, and a comprehensive accessibility strategy. The footwear prioritizes practicality and usefulness, ensuring safety, comfort, and autonomy for visually impaired students. The customizable replaceable soles enhance stability on various terrains, reducing the risk of falls. SUPPER SOLE represents a groundbreaking advancement in footwear technology for visually impaired students, promoting inclusivity and accessibility, enabling them to navigate their educational environments with greater ease and independence.